Kewenangan Badan Penyelesaian Sengketa Konsumen dalam Sengketa Perbankan: Analisis Putusan MA Nomor 253 K/Pdt.Sus-BPSK/2017 - Parinduri, Muhammad Ali Hadidie (Civil Officium: Journal of Empirical Studies on Social Science, 2025)
This study examines the validity of the Consumer Dispute Settlement Agency’s (BPSK) authority in handling banking disputes, as reflected in the Supreme Court Decision No. 253 K/Pdt.Sus-BPSK/2017. The aim is to analyze the legal scope of BPSK’s jurisdiction over conflicts between consumers and financial service institutions. The research employs a normative juridical approach with a descriptive-analytical method, using secondary data from primary, secondary, and tertiary legal sources. The study is library-based, with legal documents as the primary source. Data were analyzed qualitatively using descriptive analysis. Findings show that arbitration-based banking dispute resolution falls under the authority of the Financial Services Sector Alternative Dispute Resolution Body, as regulated by Law No. 21 of 2011 and POJK No. 1/POJK.07/2014. The Supreme Court concluded that BPSK has no absolute jurisdiction over banking breach of contract cases, thus annulling BPSK’s decision in the case in question. The study highlights the importance of institutional accuracy in dispute resolution to ensure valid legal protection for involved parties.